1996
DOI: 10.1038/nbt0896-1021
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-linked oligonucleotide assay

Abstract: The recent development of in vitro methods to select high-affinity ligands by combinatorial chemistry methodologies promises unique and theoretically unlimited supplies of novel therapeutic and diagnostic reagents. One such combinatorial chemistry process, systematic evolution of ligands by exponential enrichment (SELEX), allows rapid identification, from large random sequence pools, of the few oligonucleotide sequences that bind to a desired target molecule with high affinity and specificity. We describe an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
204
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(207 citation statements)
references
References 42 publications
0
204
0
3
Order By: Relevance
“…Drolet et al 26 reported the first enzyme-linked aptamer assay (ELAA) consisting of a mixed ELISA/ELAA sandwich to detect human vascular endothelial growth factor on a microtiter plate. Since then, similar assays have been used with either labeled or immobilized nucleic acid molecules as capturing or detecting agents.…”
Section: Discussionmentioning
confidence: 99%
“…Drolet et al 26 reported the first enzyme-linked aptamer assay (ELAA) consisting of a mixed ELISA/ELAA sandwich to detect human vascular endothelial growth factor on a microtiter plate. Since then, similar assays have been used with either labeled or immobilized nucleic acid molecules as capturing or detecting agents.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62] Target binding to immobilized aptamers may also increase the mass or refractive index nearby the surface ( Figure 3A). [63][64][65] However, simple binding based assays require extensive washing.…”
Section: Biosensor Design Strategiesmentioning
confidence: 99%
“…DNA15-coated beads were used to detect α-thrombin in human serum. The detection method (a sandwich immunoassay) was analogous to that described by Drolet et al 26 for the enzyme-linked immunosorbent assay (ELISA)-based detection of vascular endothelial growth factor (VEGF) in a serum sample. The thrombin assay was both specific and sensitive, allowing detection of α-thrombin in a serum dilution as low as 0.125%.…”
Section: Discussionmentioning
confidence: 99%